COHERENCE DISCOURSE STRATEGY OF PASAMBAHAN:MINANGKABAU CULTURAL DISCOURSE - NFN Widya (Masyarakat Linguistik Indonesia, 2020)
Pasambahan is one of well-known spoken discourse in Minangkabau. It is a medium for demonstrating speaking skills between the spokesperson of the host and the guests in several traditional events in Minangkabau. This research seems important to reveal the existence of symptoms of cohesion and semantic coherence in pasambahan discourse in Minangkabau ceremonies. Therefore, this present research aimed to find out the cohesive devices of the coherence relationship and the ways to achieve coherence in pasambahan. These two problems will be examined in terms of discourse analysis. Halliday and Hasan (1979) and Oshima and Hogue (2006) are reviewed to identify their claims about cohesion and coherence and apply them in pasambahan. The document review technique, which is one of the qualitative research methods, is employed in the study. The data in the form text of pasambahan were taken from written source, that is, pasambahan makan minum ‘Pasambahan done before starting the banquet’ taken from Minangkabau Panitahan Adat Alur book by Jamilus Jamin (2006). The results show that as a discourse, pasambahan shows symptoms of cohesion and coherence. The text coherence is achieved in several ways, namely (1) reiteration of key words, (2) the use of consistent pronoun, (3) the use of conjunction, and (4) arranging ideas in chronological order Ways 1 to 3 show a big role of cohesive devices in achieving text coherence, that is, the pattern of coherence that emerges is the coherence marked by linguistics units. Hence, it is an explicit relationship. Some marke rs found are repetition, synonymy, antonymy, pronoun, and conjunction. The coherence relationship can occur between words, phrases, clauses, and sentences. However, the way 4 shows the symptoms of coherence achieved without lingual markers (implicit), meaning that coherence is achieved through semantic relationships between sentences forming the text.